Photopatch Testing in Chinese Patients Over 10 Years. Issue 3 (May 2016) - Hu, Yue; Wang, Duoqin; Shen, Yanyun; Tang, Hui
Abstract : Background: Photoallergic contact dermatitis (PACD) is a hypersensitivity reaction that occurs when a previously photosensitized exogenous agent comes into contact with UV radiation. The best method for testing PACD is photopatch testing (PPT). Objectives: The primary objective of the study was to determine the frequency of PACD to 20 different photoallergens in common usage in China during a 10-year period. Methods: All patients (n = 6153) who had PPTs done between 2005 and 2014 at the Department of Dermatology of Huashan Hospital, Fudan University, were included. Results: A total of 3767 PACD reactions in 3668 subjects (59.61%) were recorded. Of these allergens, chlorpromazine (CPZ) (51.82%), para-aminobenzoic acid (11.94%), thimerosal (9.81%), potassium dichromate (6.37%), sulfanilamide (5.38%), and formaldehyde (4.7%) were the top 6 allergens that elicited PACD reactions. A comparison of PACD reactions between January 2005 to December 2009 and January 2010 to December 2014 revealed a statistically significant decrease in PACD reaction for chlorpromazine, potassium dichromate, p -aminobenzoic acid, and p -phenylenediamine. Formaldehyde showed a trend toward a statistically significant increase in sensitization over the 10-year period. Conclusions: In conclusion, positive PACD reactions were most frequent to chlorpromazine in our population. New allergens such as potassium dichromate and formaldehyde should be added to the test series.